Genome-wide mapping of DNase I hypersensitive sites and association analysis with gene expression in MSB1 cells - He, Yanghua; Carrillo, Jose A.; Luo, Juan; Ding, Yi; Tian, Fei; Davidson, Irit; Song, Jiuzhou (Frontiers in Genetics, 2014)
DNase I hypersensitive sites (DHSs) mark diverse classes of cis-regulatory regions, such as promoters and enhancers. MSB-1 derived from chicken Marek's disease (MD) lymphomas is an MDV-transformed CD4+ T-cell line for MD study. Previously, DNase I HS sites were studied mainly in human cell types for mammalian. To capture the regulatory elements specific to MSB1 cells and explore the molecular mechanisms of T-cell transformation caused by MDV in MD, we generated high-quality of DHSs map and gene expression profile for functional analysis in MSB1 cell line. The total of 21,724 significant peaks of DHSs was identified from around 40 million short reads. DHSs distribution varied between chromosomes and they preferred to enrich in the gene-rich chromosomes. More interesting, DHSs enrichments appeared to be scarce on regions abundant in CpG islands. Besides, we integrated DHSs into the gene expression data and found that DHSs tended to enrich on high expressed genes throughout whole gene regions while DHSs did not show significant changes for low and silent expressed genes. Furthermore, the correlation of DHSs with lincRNAs expression was also calculated and it implied that enhancer-associated lincRNAs probably originated from enhancer-like regions of DHSs. Together, our results indicated that DNase I HS sites highly correlate with active genes expression in MSB1 cells, suggesting DHSs can be considered as markers to identify the cis-regulatory elements associated with chicken Marek’s disease.